2010
DOI: 10.1111/j.1749-6632.2010.05491.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of ocular sulfur mustard injury: development of a model system

Abstract: Exposure of tissues to sulfur mustard (SM) results in the formation of protein and nucleotide adducts that disrupt cellular metabolism and cause cell death. Subsequent pathologies involve a significant proinflammatory response, disrupted healing, and long-term defects in tissue architecture. Following ocular exposure, acute corneal sequelae include epithelial erosions, necrosis, and corneal inflammation. Longer term, a progressive injury becomes distributed throughout the anterior chamber, which ultimately cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 20 publications
4
54
0
Order By: Relevance
“…The persistent neovascularization which remained elevated at 56 day post-exposure indicates oxygen deprivation as well as persistent inflammation and injury to the cornea causing loss of transparency and vision problems. Edema and corneal thickness are also reported following SM exposure, which peaked by 7 days post-exposure (10, 22-24), and consistent with that, corneal thickness was maximal at 1-7 days post LEW exposure indicating edema and inflammation. LEW at both 2.5 and 7.5 min exposure durations caused swelling and redness of the conjunctiva and iris, which resolved simultaneously at 4-14 days post-exposure; these injuries have been reported with both LEW and SM (10, 15, 22).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The persistent neovascularization which remained elevated at 56 day post-exposure indicates oxygen deprivation as well as persistent inflammation and injury to the cornea causing loss of transparency and vision problems. Edema and corneal thickness are also reported following SM exposure, which peaked by 7 days post-exposure (10, 22-24), and consistent with that, corneal thickness was maximal at 1-7 days post LEW exposure indicating edema and inflammation. LEW at both 2.5 and 7.5 min exposure durations caused swelling and redness of the conjunctiva and iris, which resolved simultaneously at 4-14 days post-exposure; these injuries have been reported with both LEW and SM (10, 15, 22).…”
Section: Discussionsupporting
confidence: 83%
“…Edema and corneal thickness are also reported following SM exposure, which peaked by 7 days post-exposure (10, 22-24), and consistent with that, corneal thickness was maximal at 1-7 days post LEW exposure indicating edema and inflammation. LEW at both 2.5 and 7.5 min exposure durations caused swelling and redness of the conjunctiva and iris, which resolved simultaneously at 4-14 days post-exposure; these injuries have been reported with both LEW and SM (10, 15, 22). Importantly, though the gross features of LEW-induced ocular injury in the present study in rabbits were observed within 6 h post-exposure, these lesions in rabbits including corneal injuries were observed 24-48 h post SM exposure (21, 25).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite imminent threats and devastating ocular injuries by vesicating agents 611 , effective therapies suitable in case of a mass casualty are not established. This is primarily due to the lack of defined mechanisms contributing to pathological and clinical progression of ocular injuries by vesicants in relevant animal models.…”
Section: Introductionmentioning
confidence: 99%
“…The rabbit cornea is structurally similar to that of the human, and at functionally equivalent doses, rabbit and human eyes exhibit nearly identical lesions (Mann and Pullinger, 1944;Gates and Moore, 1946). Recently, a rabbit vapor HD exposure model has been shown to produce dose-dependent, multiphasic corneal injuries with sequelae similar to those observed in human victims (Kadar et al, 2001;Milhorn et al, 2010;McNutt et al, 2012a,b).…”
Section: Mechanistic Studies Of Hd Toxicitymentioning
confidence: 88%